ADVANTAGES OF MODERN DIAGNOSTIC METHODS FOR TYPES OF ARTHRITIS - Ubaydullaev Rustam (American Journal of Bioscience and Clinical Integrity, 2024)
A joint is a connection between two or more bones separated by a space. The joint is covered with a synovial membrane, which moisturizes and protects the articular surfaces of the bones. They, in turn, are covered with cartilage tissue (cartilage). This design allows the bones to move and not rub against each other.